COX-2 overexpression in resected pancreatic head adenocarcinomas correlates with favourable prognosis - Pomianowska, Ewa (BMC Cancer, 2014)
BACKGROUND: Overexpression of cyclooxygenase-2 (COX-2) has been implicated in oncogenesis and progression of adenocarcinomas of the pancreatic head. The data on the prognostic importance of COX expression in these tumours is inconsistent and conflicting. We evaluated how COX-2 overexpression affected overall postoperative survival in pancreatic head adenocarcinomas. METHODS: The study included 230 consecutive pancreatoduodenectomies for pancreatic cancer (PC, n = 92), ampullary cancer (AC, n = 62) and distal bile duct cancer (DBC, n = 76). COX-2 expression was assessed by immunohistochemistry. Associations between COX-2 expression and histopathologic variables including degree of differentiation, histopathologic type of differentiation (pancreatobiliary vs. intestinal) and lymph node ratio (LNR) were evaluated. Unadjusted and adjusted survival analysis was performed. RESULTS: COX-2 staining was positive in 71% of PC, 77% in AC and 72% in DBC. Irrespective of tumour origin, overall patient survival was more favourable in patients with COX-2 positive tumours than COX-2 negative (p = 0.043 in PC, p = 0.011 in AC, p = 0.06 in DBC). In tumours of pancreatobiliary type of histopathological differentiation, COX-2 expression did not significantly affect overall patient survival. In AC with intestinal differentiation COX-2 expression significantly predicted favourable survival (p = 0.003). In PC, COX-2 expression was significantly associated with high degree of differentiation (p = 0.002). COX-2 and LNR independently predicted good prognosis in a multivariate model. CONCLUSIONS: COX-2 is overexpressed in pancreatic cancer, ampullary cancer and distal bile duct cancer and confers a survival benefit in all three cancer types. In pancreatic cancer, COX-2 overexpression is significantly associated with the degree of differentiation and independently predicts a favourable prognosis.